From Emergent to Multiliteracies: A Review of Preschool Language Teaching Curricula in Greece (1989–2021) - Theodoropoulos, Emil; Tsakanika, Stavroula (International Journal of Language and Literary Studies, 2026)
The purpose of this paper is to review the modern curricula of language teaching in Greek preschool education, tracing their evolution from the landmark 1989 syllabus to the implementation of the new 2021 curriculum. The study employs a qualitative policy document analysis of official preschool language curricula issued by the Greek Ministry of Education in collaboration with the Institute of Educational Policy (IEP), between 1989 and 2021. The review analyzes the key pedagogical and theoretical shifts that have shaped early childhood language education over three decades. It follows the progression from a didactic, skills-based model to the introduction of child-centered, interdisciplinary methods and the concept of "emergent literacy" in 2003. The analysis then highlights the formal integration of "critical literacy" as a core theoretical approach in the 2014 revision, culminating in the adoption of a comprehensive "multiliteracies" framework in the 2021 curriculum. The findings demonstrate a clear and progressive trajectory towards a more sophisticated, theoretically-grounded framework that views literacy as a complex, socially-situated practice. This evolution underscores a commitment to developing active, critical thinkers and reflects the understanding that high-quality preschool programs are a key pillar for a child’s success in school and in life. This review contributes to international discussions on early childhood literacy by showing how national curriculum reforms in Greece reflect broader global trends toward emergent literacy, critical literacy, and multiliteracies approaches. The review concerns Greek public kindergarten curricula for children aged 4–6, focusing on Greek as a first language.